Taking Humor Serious: Effects of Humor on Anxiety, Motivation, and Learning in Statistics - Lieck, Katrin (Faculty of Psychology, Universitas Surabaya, 2013)
Research has shown that humor and the resulting laughter can reduce tension and increase well- being. If humor could also reduce anxiety the use of it may be especially beneficial for the students in dread courses like statistics. This paper reviewed studies about the effect of humor used in statistics lectures on motivation, statistics anxiety, and learning. Results showed that humor has a positive effect on motivation and it further can reduce anxiety. Humor has also been shown to have a memory-enhancing effect but findings about the effect on learning and recall in statistics classes are inconsistent and require further research. Penelitian menunjukkan bahwa humor dan tawa yang dihasilkan dapat meredakan ketegangan dan meningkatkan rasa nyaman. Bila humor juga dapat mengurangi kecemasan, pemanfaatannya mungkin bermanfaat khususnya untuk para mahasiswa dalam kuliah menakutkan seperti statistik. Artikel ini mereview kajian-kajian tentang efek humor yang dipakai dalam kuliah statistik terhadap motivasi, kecemasan terhadap statistik, dan belajar. Hasil menunjukkan bahwa humor menimbulkan efek positif terhadap motivasi dan selanjutnya mampu mengurangi kecemasan. Humor juga telah menunjukkan mampu meningkatkan ingatan, namun temuan tentang efek terhadap belajar dan mengingat kembali dalam mata kuliah statistik tak konsisten dan membutuhkan penelitian lebih lanjut